2024
DOI: 10.1055/s-0044-1782170
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of a Bilingual Arabic-English Pittsburgh Sleep Quality Index among Adolescents and Young Adults with Good or Poor Sleep Quality

Ashokan Arumugam,
Shima A. Mohammad Zadeh,
Hanan Youssef Alkalih
et al.

Abstract: Introduction The Pittsburg Sleep Quality Index (PSQI) is widely used in different population groups to assess self-reported sleep quality over the previous month. As the Arabic language is spoken by more than 400 million people, the PSQI has been translated into Arabic for its optimal application to Arabic-speaking individuals. However, the test-retest reliability of the Arabic version of the PSQI has not been reported yet. Objective To examine the reliability and agreement of a bilingual Arabic-Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The PSQI has been routinely used in clinical practice for the assessment of sleep quality and sleep disorders. It has been found that the PSQI has a specificity of 86.5% and a sensitivity of 89.6% in differentiating between individuals with good and poor sleep quality [32]. Previous research has revealed a moderate to strong test-retest reliability of the PSQI global score among healthy adolescents and young adults [32].…”
Section: Study Tools and Outcome Measures 241 Sleep Assessment Questi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The PSQI has been routinely used in clinical practice for the assessment of sleep quality and sleep disorders. It has been found that the PSQI has a specificity of 86.5% and a sensitivity of 89.6% in differentiating between individuals with good and poor sleep quality [32]. Previous research has revealed a moderate to strong test-retest reliability of the PSQI global score among healthy adolescents and young adults [32].…”
Section: Study Tools and Outcome Measures 241 Sleep Assessment Questi...mentioning
confidence: 99%
“…It has been found that the PSQI has a specificity of 86.5% and a sensitivity of 89.6% in differentiating between individuals with good and poor sleep quality [32]. Previous research has revealed a moderate to strong test-retest reliability of the PSQI global score among healthy adolescents and young adults [32]. The PSQI distinguishes between sleep quality types to form two sleep groups for comparison.…”
Section: Study Tools and Outcome Measures 241 Sleep Assessment Questi...mentioning
confidence: 99%